STUDY EFFECT OF TAMOXIFEN ON CELL CYCLE PHASE DISTRIBUTION, IN BREAST CANCER CELLS (Journal of Pharmaceutical Negative Results, 2022)
Hormone therapy also known as estrogen suppression therapy is the first targeted therapy and is frequently used as a secondi therapeutic to lower the risk of cancer returning after surgery or spread. Tamoxifen is a drug that is commonly used to treat breast cancer by mediating estrogen receptor signaling pathways. Breast cancer is becoming a spread disease that needs a specific therapy. The main focusi of this study is the anti-cancer drug Tamoxifen (TAM)i and it’s effected on celli cycle (Culture) of breast cancer cell line measurement of cellular DNA content and the analysis of the cell cycle can be performed by flow cytometry. This study include the determination the effects of tamoxifen on MCF-7i on breast cancer celli line and investigate of the mechanism by which the affected of it on the cell cycle phases using Flowcytometric cell cycle analysis assay. As well study the Flowy cytometric cell cycle analysis of tamoxifen-treated cultures showed an increase in the proportion of cells in the GI phase of the cell cycle.